Restoration of Land Parcels using Land Consolidation & Readjustment: A Case of Resilience after Flood Disaster - Dahal, Tanka Prasad; Dangol, Susheel; Nepali, Purna Bahadur; Shrestha, Reshma (Journal on Geoinformatics, Nepal, 2023)
Millions of people are affected from natural disaster leading to loss of land tenure around the world. People affected from the disaster leading to loss of land tenure are often excluded from post disaster assistance. The parcel boundary may change or obliterated because of disaster or also from some infrastructure development. Re-establishing of the cadastral boundary is very crucial and challenging task to re-establish the tenure rights and other cadastral details. This paper focuses on the restoration of land parcels after flood. Paper highlights the impact of flood in parcel boundary and proposes a concept for restoration of those obliterated parcels of Melamchi bazar, Sindupalchok, Nepal which was affected from the flash flood on 15th June 2021. The model for restoration of land parcel using the concept of land consolidation and re-adjustment has been recommended focusing on land pooling, creating a regular shape of the parcel. This paper also evaluates the current legal provisions for restoration of land parcels after land use change due to flood.